(untitled) (Global Journal of Human-Social Science, 2016)
The first part of the paper points to the fact that the history of development of human society is largely based on violence against man and nature. Enormous differences in the development of the human community are continuing to grow creating thereby tensions in each human community and between various societies. All these developments call for changes in which man will be the subject and object of development, particularly the development of man as an individual. To that end, the model of civic initiative is suggested. Social conditions for such development should be based on relations that treat capital, knowledge and labour equally. In addition, this requires the necessary political and legislative changes based on a higher level of direct participation of the population in the creation and implementation of social community development. Accordingly, a different kind of science and different types of upbringing and education are required that will enable the heightening of both individual and collective awareness.